THE STUDENTS PERSPECTIVE IN USE GOOGLE FORM IN ENGLISH TEST AT SD KARTIKA 1-4 PEMATANGSIANTAR - Dumaris Elseria Silalahi; Tio Lestari Simanjuntak; Lusia Pebriyani Silaban (Adisam Publisher, 2026)
This study looks into students' thoughts on the use of Google Forms as a learning assessment tool in English language assessments. The research employed a quantitative methodology using questionnaires to gather data from fifth-grade students at SD KARTIKA 1-4 Pematangsiantar. The study focused on three key aspects of Google Forms: attractiveness, accessibility, and effectiveness. Due to the data, students generally found Google Forms attractive, with most of them like the platform's display. . However, accessibility posed challenges, with students reporting difficulties operating Google Forms, experiencing interruptions due to slow internet connections, and expressing concerns about the potential for cheating. Regarding effectiveness, students found Google Forms facilitated understanding of English test questions and preferred it over traditional paper-based tests. They also felt more confident answering questions using Google Forms. However, the immediate feedback provided by Google Forms caused anxiety for some students. . The study concludes that while Google Forms offers advantages in terms of convenience and accessibility, Challenges connected to internet access, technological concerns, and the possibility for cheating must be overcome to ensure its successful and equitable use in educational contexts. The findings highlight the importance of considering students' perspectives when integrating digital assessment tools into the learning process and underscore the need for ongoing efforts to improve the accessibility and reliability of such technologies.